Using the theory of planned behaviour to determine radiation protection among South African diagnostic radiographers: a cross‐sectional survey - Shantel Lewis; Charlene Downing; Christopher M Hayre (Journal of Medical Radiation Sciences, 2022)
Abstract Introduction The use of ionising radiation in medicine accounts for the majority of radiation exposure from artificial sources. Therefore, all measures to safeguard against unnecessary radiation exposure must be taken. As radiographers are central to radiation protection, this study aimed to determine South African radiographers’ attitude towards radiation protection, subjective norm and perceived behavioural control concerning radiation protection. Methods This quantitative cross‐sectional study used an online theory of a planned behaviour radiation protection questionnaire shared through social media platforms from August 2019 to February 2020. Diagnostic radiographers registered with the Health Professions Council of South Africa and employed at radiology departments in South Africa were invited to participate in the study. Results Four hundred and seventeen radiographers in South Africa responded to the questionnaire. The majority of respondents (90%, n = 376) plan to use radiation protection; however, only 16% continuously used radiation protection in the past. Respondents felt that using radiation protection was extremely good (72.2%), pleasant (47%), beneficial (74.1%), rewarding (55.2%) and worth the time (52.5%); 57% of respondents indicated that using radiation protection takes longer to complete the examination. Respondents report that approval from patients (43.5%), patients’ family (32%), radiographer coworkers (31%), radiology managers (47%) and radiologists (43.9%) is very much important to them. Conclusion The study shows that even though fewer respondents use radiation protection at present, most respondents plan and intend to use radiation protection measures. Respondents felt that radiation protection was good and beneficial, with some respondents feeling that radiation protection is not worth the time, which coincide with lengthening the examination. Overall, South African radiographers’ attitudes towards radiation protection, subjective norm, perceived behavioural control and radiation protection intention were high.